ANALISIS DINDING PENAHAN TANAH PADA RUAS JALAN TRANS SERAM DESA LUMOLI KABUPATEN SERAM BAGIAN BARAT - Hatulesila, Kezia; Latar, Sjafrudin; Johannes, Standy (Jurusan Teknik Sipil, 2024)
The Trans Seram road section of Lumoli Village, West Seram Regency has a length of 7,150m and a width of 6m starting from STA 0+000 to STA 7+150. Along the road section there are four landslide points, namely at STA 0+350, STA 1+850, STA 2+600 and STA 3+615. Of the four avalanche points, there are three points that have been handled and the remaining one point has not been handled. The avalanche problem at STA 3+615 - STA 3+650 occurs along 35m with a slope height of 6m already covering the road body ± 4.2m remaining 1.8m. This greatly disrupts the activities of road users because it causes narrowing of the road body and temporary avalanche handling using used asphalt dromes. The purpose of this research is to determine the dimensions and stability of retaining walls against shear, overturning and soil bearing capacity on the Lumoli village trans seram road section. The planning of retaining walls on the trans seram road section of Lumoli village uses a cantilever type with a height of no more than 6-7m as a structure to prevent soil collapse by using rankine theory to calculate lateral soil pressure. The results of the dimensions of the cantilever type retaining wall H = 4m, H1 = 3.52m, H2 = 0.48m, Df = 0.8m, H2 = 16m, H22 = 0.23m, A = 0.66, b = 0.3m, C = 1.18m, D = 0.66m, B = 2.8m. And the results of stability against overturning = 3.027 ≥1.5 Safe, stability against shear = 2.910 ≥1.5 Safe and stability against bearing capacity = 809.045 Kn/m2.